Assessment of the application for renewal of authorisation of PHYZYME® XP 5000 G/L (6‐phytase) for chickens for fattening, laying hens, turkeys for fattening, ducks for fattening, weaned piglets, pigs for fattening and sows for reproduction. (16th May 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: PHYZYME ® XP 5000 G/L is a feed additive that contains 6‐phytase produced by a genetically modified strain of Schizosaccharomyces pombe . The applicant requested for the renewal of the authorisation for PHYZYME ® XP 5000 G and L to be used as a feed additive in chickens for fattening, laying hens, turkeys for fattening, ducks for fattening, piglets (weaned), pigs for fattening and sows. This scientific opinion concerns the renewal of the authorisation of the additive for those species. To support the request, the applicant provided evidence that the additive in the market complies with the conditions of the authorisation. According to the information provided by the applicant, no new evidence has been identified that would make the FEEDAP Panel reconsider the previous conclusions regarding the safety for the target species, consumer, user and environment. The application for renewal of the authorisation did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.